1999
DOI: 10.1159/000025415
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant Tachyarrhythmias in Right Atria of Cardiomyopathic versus Healthy Syrian Hamster

Abstract: We studied the role of acetylcholine (ACh) and calcium overload in the induction of atrial flutter or atrial fibrillation (AF) in right atria from 34 normal male Syrian hamsters (F1B) and 33 cardiomyopathic Syrian hamsters (BIO 14.6) associated with focal myocardial necrosis. Action potential (AP) was recorded with conventional microelectrode techniques and twitch force by a transducer. ACh (0.1, 1 and 10 μM) induced high-frequency AF (around 33 Hz) along with tension oscillations and contracture in 7 of 12 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The effects of rapid atrial contrast to atrial flutter which, although it could have very pacing on the triggered points of PVs are not clear. In this high-frequency firings similar to those of atrial fibrillation study, there was a higher incidence of spontaneously [22], consisted of rather uniform APs [13,23].…”
Section: Electrical Activity Of Pulmonary Veinssupporting
confidence: 68%
See 1 more Smart Citation
“…The effects of rapid atrial contrast to atrial flutter which, although it could have very pacing on the triggered points of PVs are not clear. In this high-frequency firings similar to those of atrial fibrillation study, there was a higher incidence of spontaneously [22], consisted of rather uniform APs [13,23].…”
Section: Electrical Activity Of Pulmonary Veinssupporting
confidence: 68%
“…A circulation water blanket and controldepolarization (V ) was determined by electronic difmax ler were used to maintain body temperature at 37618C. ferentiation as previously described [13]. Electrical stimuli The chest was opened through the right fifth intercostal of 2-ms duration with a suprathreshold strength (30% space.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent findings in isolated ventricular muscles that the magnitude of post‐rest potentiation of contractile force 20 in myopathic myocardium was much smaller than that in healthy control myocardium 21 are in agreement with this assumption. The diminished arrhythmogenic I ti in myopathic ventricular myocytes are in accordance with the lower incidence of tachyarrhythmias observed in the hereditary myopathic right atria 9 …”
Section: Discussionsupporting
confidence: 74%
“…However, in our previous experiments on the right atria of myopathic compared with healthy hamsters, 9 we found that myopathic right atria were less likely to develop tachyarrhythmias induced by a brief, high‐frequency pacing (32 Hz) or when the [Ca 2+ ] of the superfusate was increased from 2.7 to 8.1 mmol/L and [K + ] was reduced from 4 to 1 mmol/L. We had demonstrated previously that, in cardiac tissues and myocytes superfused in a high [Ca] o –low [K] o solution, delayed afterdepolarizations (DAD), aftercontractions and oscillatory transient inward currents (I ti ) could develop during diastole in various animal models 10–12 as a consequence of [Ca 2+ ] i overload 3 .…”
Section: Introductionmentioning
confidence: 92%
“…Lin et al [11] extended these findings by reporting that normal atria are more susceptible than myopathic atria to the induction of tachyarrhythmias by acetylcholine or by sodium-dependent high-frequency pacing. However, calcium overload does not seem to play an essential role in the initiation of atrial fibrillation.…”
Section: Reduced Tachyarrhythmia During Cardiomyopathymentioning
confidence: 94%